(untitled) (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2026)
This article analyzes the integration of linguistic science and artificial intelligence (AI) technologies, as well as the new conceptual tasks and research directions facing linguists in the era of Large Language Models (LLMs). The study examines the role of linguistic theories in developing mathematical language models, the importance of cognitive linguistics in AI architecture, and the fundamental challenges of digitalizing the Uzbek language. The article concludes with insights into the new competencies required for modern linguistic experts and future scientific research trajectories.